The Effect of eight weeks of aerobic exercise on quality of life and pain in patients with rheumatoid arthritis - Navid Kalaly Jouneghani; Nader Rahnama; Effat Bambaeichi; Yasser Jafari; Zahra Riahi (Vesnu Publications, 2011)
Background: Rheumatoid arthritis is an inflammatory disease in which joint pain is considered as the most important problem for those with the disease. Joint pain and stiffness cause low mobility in affected people which eventually will result in reduced quality of their life. The aim of this study was to determine the effect of an 8-week aerobic exercise on the quality of life and the level of pain in patients with rheumatoid arthritis. Materials and methods: In this study, patients with rheumatoid arthritis (age range 38 to 65 years) who was referred to and subsequently treated in AL Zahra Hospital (Isfahan-Iran) and their medication did not change during study period were examined. Of this population, those patients who had no experience of attending any sporting activity during the six months prior to the study period and had neither acute and chronic diseases nor mental and psychological problems were selected as the subjects of this study (n = 23). Subjects were randomly assigned to control (n = 12) and experimental (n = 11) groups. Patients in experimental group underwent an 8-week aerobic exercise program while the control group did not receive any exercise program. Quality of life of patients was measured using the short form 36 (SF36) and visual linear scale was used to assess their pain. Quality of life and pain of all patients evaluated before the initiation and after completion of the 8-week program. Results: The results of this study showed that compared to the scores obtained at the beginning of the program, a significant improvement of quality of life scores at the end of intervention in the experimental group (p<0.01), but no such difference was observed in the control group (p>0.05). A significant reduction in pain levels was observed in the experimental group (p<0.05) while there was not any significant reduction of pain in the control group (p>0.05). Conclusions: It can be concluded that aerobic exercise can reduce pain in patients with rheumatoid arthritis and improve the quality of their life. Therefore it can be considered as an appropriate treatment regimen for such patients. Key words: Aerobic exercise, Rheumatoid arthritis, Pain, Quality of life